Economic Valorisation of the Freight Transport Centre Kutina - Badanjak, Dragan; Žmegač, Davor; Kaužljar, Dražen (Promet - Traffic&Transportation, 2012)
The paper analyses the conditions for constructing a freight- transp01t centre in Kutilza with special emphasis on the positiveinfluences that such a project could have for the town ofKutina and the Moslavina region. The analysis of the locationhas shown that the conditions for its establishment have beenmet, provided that town administration determines the ways inwhich the project will be realised regarding the necesswy financialscheme.